Assuring your family business a long life - Ward, John L.; Jossey-Bass Publishers (San Francisco, CA. : Jossey-Bass Publishers, 1990)
The programs contains the information regarding the family business includes the critical issues, preparing, sustaining and lessons from successful family business
Critical issues for your family business -- Preparing the family mission statement and participation plan -- Sustaining the business through family meetings -- Lessons from successful family businesses
Keywords: Family corporations -- Management